2009
DOI: 10.1577/t07-252.1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Habitat Associations of Radio‐Tagged Adult Lost River Suckers and Shortnose Suckers in Upper Klamath Lake, Oregon

Abstract: Radiotelemetry was used to investigate the summer distribution and diel habitat associations of endangered adult Lost River suckers Deltistes luxatus and shortnose suckers Chasmistes brevirostris in northern Upper Klamath Lake, Oregon. From 2002 to 2004, Lost River and shortnose suckers were tracked by boat, and water depth and water quality were measured at each fish location. A series of water quality monitors were deployed in northern Upper Klamath Lake to provide temporal information on ambient temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…As the bloom declines and cells senesce in late July to early August, oxygen may be depleted in the water column and lakebed. These suboxic conditions are thought to negatively affect the survival of the adult and possibly the juvenile life stages of two sucker species (Catostomidae) that traditionally were harvested by native peoples but have been listed as endangered since 1988: shortnose suckers (Chasmistes brevirostris) and Lost River suckers (Deltistes luxatus) ( [24][25][26][27]; see also http://pubs. usgs.gov/of/2010/1261/).…”
Section: Site Descriptionmentioning
confidence: 99%
“…As the bloom declines and cells senesce in late July to early August, oxygen may be depleted in the water column and lakebed. These suboxic conditions are thought to negatively affect the survival of the adult and possibly the juvenile life stages of two sucker species (Catostomidae) that traditionally were harvested by native peoples but have been listed as endangered since 1988: shortnose suckers (Chasmistes brevirostris) and Lost River suckers (Deltistes luxatus) ( [24][25][26][27]; see also http://pubs. usgs.gov/of/2010/1261/).…”
Section: Site Descriptionmentioning
confidence: 99%
“…Finally, more research is needed to determine whether specific environmental conditions, such as poor water quality, loss of deep water refugia, limited access to spawning tributaries, and/or poor fish condition, are associated with sucker susceptibility to bird predation in the Upper Klamath Basin. Banish et al (2009) observed poor water quality (low dissolved oxygen, high pH, and outbreaks of the cyanobacterium, Aphanizomenon flos-aquae) and habitat conditions in parts of Upper Klamath Lake, which caused suckers to congregate in large numbers in areas where they might have been more susceptible to bird predation. Hewitt and Hayes (2013) noted that spawning runs into Willow Creek, the lone spawning tributary for Shortnose Suckers and Lost River Suckers in Clear Lake, were limited when flows were low in the creek as a result of drought conditions.…”
mentioning
confidence: 99%
“…Adult Lost River sucker appear to inhabit slightly deeper habitats than adult shortnose sucker. Banish et al (2009) found that based on 50% kernel estimates, radio-tagged Lost River sucker were often associated with relatively deeper areas (e.g., immediately off of Ball Point and Eagle Ridge Point), whereas shortnose sucker tended to be more often associated with areas relatively near the shoreline.…”
Section: Ecological Statusmentioning
confidence: 99%